Expression of granulocyte-colony-stimulating factor and its receptor in human Ewing sarcoma cells and patient tumor specimens: potential consequences of granulocyte-colony-stimulating factor administration - Morales Arias, Jaime (2007)
BACKGROUND: Ewing sarcoma (ES) is a highly vascular malignancy. It has been demonstrated that both angiogenesis and vasculogenesis contribute to the growth of ES tumors. Granulocyte-colony-stimulating factor (G-CSF), a cytokine known to stimulate bone marrow (BM) stem cell production and angiogenesis, is routinely administered to ES patients after chemotherapy. Whether ES cells and patient tumor samples express G-CSF and its receptor (G-CSFR) and whether treatment with this factor enhances tumor growth was examined. METHODS: Human ES cell lines were analyzed for expression of G-CSF and G-CSFR in vitro and in vivo. Sixty-eight paraffin-embedded and 15 frozen tumor specimens from patients with ES were also evaluated for the presence of G-CSF and G-CSFR. The in vivo effect of G-CSF on angiogenesis and BM cell migration was determined. Using a TC/7-1 human ES mouse model, the effect of G-CSF administration on ES tumors was investigated. RESULTS: G-CSF and G-CSFR protein and RNA expression was identified in all ES cell lines and patient samples analyzed. In addition, G-CSF was found to stimulate angiogenesis and BM cell migration in vivo. Tumor growth was found to be significantly increased in mice treated with G-CSF. The average tumor volume for the group treated with G-CSF was 1218 mm(3) compared with 577 mm(3) for the control group (P = .006). CONCLUSIONS: The findings that ES cells and patient tumors expressed both G-CSF and its receptor in vitro and in vivo and that the administration of G-CSF promoted tumor growth in vivo suggest that the potential consequences of G-CSF administration should be investigated further